PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DENGAN ANGGARAN SEBAGAI ALAT PENGENDALIAN BIAYA (STUDI KASUS PADA CV. CITRA NIAGA CEMERLANG BAUBAU - Mutmainnah, Mutmainnah (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
This study aims to determine the application of accountability accounting with budget as a cost control tool at CV Citra Niaga Cemerlang Baubau. The population that is used as the target of this research is cost control, the data analysis used is descriptive analysis. The results of the study indicate that the application of corporate responsibility accounting has not been adequate. This is supported by the non-fulfillment of indicators for the application of accountability accounting at CV Citra Niaga Cemerlang Baubau which has compiled an organizational structure quite well. This can be seen from the existence of a clear description of the division of authority and responsibility for each level of management and working relationships between sections within the company. The existence of an organizational structure allows the success of the planning and control programs set by the company.